Exploring the Potential of Ellagic Acid in Gastrointestinal Cancer Prevention: Recent Advances and Future Directions - Abhishek Chauhan; Monika Yadav; Ritu Chauhan; Rupesh Kumar Basniwal; Vinay Mohan Pathak; Anuj Ranjan; Raj Kishor Kapardar; Rajpal Srivastav; Hardeep Singh Tuli; Seema Ramniwas; Darin Mansor Mathkor; Shafiul Haque; et al. (Oncology and Therapy)
Abstract Gastrointestinal (GI) cancers are a significant global health concern with diverse etiologies and limited treatment options. Ellagic acid (EA), a natural polyphenolic compound, exhibits promising anticancer properties against various GI malignancies. In this article, we have reviewed recent research on the anticancer potential of EA across esophageal, gastric, colorectal, pancreatic, and liver cancers. In esophageal cancer, EA inhibits the formation of O6-methylguanine (O6-meGua) adducts induced by carcinogens like N-nitrosomethylbenzylamine (NMBA), thereby suppressing tumor growth. Additionally, EA inhibits STAT3 signaling and stabilizes tumor suppressor proteins, showing potential as an anti-esophageal cancer agent. In gastric cancer, EA regulates multiple pathways involved in cell proliferation, invasion, and apoptosis, including the p53 and PI3K-Akt signaling pathways. It also demonstrates anti-inflammatory and antioxidant effects, making it a promising therapeutic candidate against gastric cancer. In colorectal cancer (CRC), EA inhibits cell proliferation, induces apoptosis, and modulates the Wnt/β-catenin and PI3K/Akt pathways, suggesting its efficacy in preventing CRC progression. Furthermore, EA has shown promise in pancreatic cancer by inhibiting nuclear factor-kappa B, inducing apoptosis, and suppressing epithelial–mesenchymal transition. In liver cancer, EA exhibits radio-sensitizing effects, inhibits inflammatory pathways, and modulates the tumor microenvironment, offering potential therapeutic benefits against hepatocellular carcinoma. Studies on EA potential in combination therapies and the development of targeted delivery systems are required for enhanced efficacy against gastrointestinal cancers.